2010
DOI: 10.1038/tpj.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

VEGF −460T → C polymorphism and its association with VEGF expression and outcome to FOLFOX-4 treatment in patients with colorectal carcinoma

Abstract: The -460T → C polymorphism of vascular endothelial growth factor (VEGF) gene significantly increases its promoter activity. A pilot study was conducted to assess the influence of this polymorphism on clinicopathological features of patients with colorectal carcinoma. In total, 228 patients were enrolled, including 100 with stage II/III colorectal carcinoma receiving curative surgery and 128 with metastatic disease. An excellent correlation in VEGF -460 genotypes based on white blood cells and tumor tissues exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…First, the study could not address the mechanism of how the VEGF polymorphisms influence the survival outcomes of lung cancer patients. Previous study demonstrated a good correlation between TC/CC genotypes of the VEGF -460 T > C polymorphism and increased serum VEGF levels in colorectal cancer patients [21]. An increased serum VEGF expression was also observed in ovarian cancer patients carrying -634 C allele [22].…”
Section: Discussionmentioning
confidence: 98%
“…First, the study could not address the mechanism of how the VEGF polymorphisms influence the survival outcomes of lung cancer patients. Previous study demonstrated a good correlation between TC/CC genotypes of the VEGF -460 T > C polymorphism and increased serum VEGF levels in colorectal cancer patients [21]. An increased serum VEGF expression was also observed in ovarian cancer patients carrying -634 C allele [22].…”
Section: Discussionmentioning
confidence: 98%
“…In colorectal cancer, VEGF promoter polymorphisms predict response and time to progression with anti-VEGF therapy (Pander et al 2010). However, promoter polymorphisms have similar predictive power with chemotherapy regimens lacking an anti-VEGF component (Chen et al 2010a). Similar results are obtained in lung cancer (Heist et al 2008).…”
Section: Common Polymorphisms In Angiogenesismentioning
confidence: 61%
“…A correlation between the presence of a specific allele on a polymorphic site and the expression of the respective protein has been previously documented for VEGF [22], [23]. SNPs in regulatory sequences, such as introns and 5′ and 3′ UTRs, have been shown to alter mRNA stability [24], [25] processing efficiency [26], isoform expression [27], [28] and localization [29].…”
Section: Methodsmentioning
confidence: 93%